ChanceMINT.NRW - Studienbiografische Wendepunkte und Karriereperspektiven - Auferkorte-Michaelis, Nicole; Gillert, Arne (Verlag Barbara Budrich, 2017)
The ChanceMINT.NRW project provides insights into professional practice, prepares students for their career entry and motivates them to shape the course of their studies with self-confidence. Together with partners from industry, committed female students visit major construction sites, sewage treatment plants and planning offices and talk to experts from partner companies about hurdles, successes and professional challenges.